FREQUENCY OF METABOLIC SYNDROME IN PATIENTS WITH TYPE-2 DIABETES - Ahmed, Nasir; Ahmad, Tauqir; Hussain, Syed Javed; Javed, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Diabetes, Hypertension, Obesity and Ischaemic Heart Disease have become a problem of public health magnitude with substantial economic burden both in the developed as well as the developing countries. Obesity is quite frequent in Type 2 diabetics and also plays a central role in causing Metabolic Syndrome (MetS). Metabolic Syndrome significantly increases the incidence of cardiovascular complications. This study was done to determine the frequency of MetS in our Type 2 diabetic patients as most of the components of MetS can be modified and identifying/managing these at an early stage might be of considerable help in reducing cardiovascular complications. Methods: This cross-sectional study was done in Medical '˜B' and Medical '˜A' wards of Ayub Teaching Hospital, Abbottabad from Nov, 08 to April, 09. Type 2 Diabetic patients aged above 40 years who gave informed consent were included in the study. Data was collected through a structured proforma.Frequency of Metabolic Syndrome was estimated according to the IDF consensus worldwide definition of the MetS. Results: Of the 100 patients enrolled in this study 56 were females and 44 were males with a mean age of 59.9 years. Out of these 100 participants seventy six (76%) were diagnosed to have metabolic syndrome. Of the 56 females, forty eight (85.71%) were having metabolic syndrome while twenty eight (63.63%) of the 44 male participants were having the syndrome. The difference was statistically significant (p<0.05). Conclusion: Frequency of MetS was found to be significantly high in this study with female preponderance. All the components, except Hypertension were more frequent in females. Diabetic patients with metabolic syndrome need more aggressive approach in management so as to decrease the incidence of cardiovascular complications. Keywords: Metabolic Syndrome, Type 2 Diabetes Mellitus, Cardiovascular Complications